Minefield : based on the stories of six Argentine and British veterans of the Falkland war: Lou Armour, David Jackson, Ruben Otero, Sukrim Rai, Gabriel Sagastume, Marcelo Vallejo = Campo minado : basado en la historias de seis veteranos argentinos e ingleses de la guerra de Malvinas: Lou Armour, David Jackson, Ruben Otero, Sukrim Rai, Gabriel Sagastume, Marcelo Vallejo /: based on the stories of six Argentine and British veterans of the Falkland war: Lou Armour, David Jackson, Ruben Otero, Sukrim Rai, Gabriel Sagastume, Marcelo Vallejo = Campo minado : basado en la historias de seis veteranos argentinos e ingleses de la guerra de Malvinas: Lou Armour, David Jackson, Ruben Otero, Sukrim Rai, Gabriel Sagastume, Marcelo Vallejo. (2017) - Arias, Lola, 1976-
No abstract available